2012
DOI: 10.1111/rda.12103
|View full text |Cite
|
Sign up to set email alerts
|

Breed Variations in the Incidence of Pyometra and Mammary Tumours in Swedish Dogs

Abstract: Contents Dogs enrolled in a Swedish insurance company (during 1995–2006) were studied for development of pyometra and mammary tumours (MTs), with special attention to breed and age. There were over 260 000 female dogs with over 1 000 000 dog‐years at risk (DYAR) in the database, using data on bitches up to 10 years of age and 110 breeds with over 1000 DYAR. In total, 20 423 bitches were diagnosed with pyometra and 11 758 with MTs and 30 131 with either or both of the two diseases. The incidence rate (IR) for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
3
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 8 publications
5
79
3
11
Order By: Relevance
“…However, the possibly increased risk of offspring developing pyometra should be considered because large breed variations in the incidence of pyometra have been shown, which indicates that there may be genetic factors predisposing for the disease [1]. The owners should also be informed that the risk of recurrence is higher for a bitch that is 5 years or older than a younger bitch.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the possibly increased risk of offspring developing pyometra should be considered because large breed variations in the incidence of pyometra have been shown, which indicates that there may be genetic factors predisposing for the disease [1]. The owners should also be informed that the risk of recurrence is higher for a bitch that is 5 years or older than a younger bitch.…”
Section: Discussionmentioning
confidence: 98%
“…On average, 19% of all insured Swedish bitches are diagnosed with pyometra before the age of 10 years [1]. In Sweden, the dog population is mainly intact [2], which is why pyometra is a frequent disorder in comparison to the situation in countries where most bitches are spayed [3].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study carried out in Japan has found that the incidence of MMT was lower in small breeds than in others (Itoh et al, 2005). A recent study performed in Sweden has observed that the breeds most frequently diagnosed with this disease were the Leonberger, Irish wolfhound, Doberman, Welsh terrier, and English springer spaniel (Jitpean et al, 2012). In Argentina, the English Cocker Spaniel, Pekingese and German shepherd have been reported as the breeds most frequently diagnosed with mammary tumors (Benavente et al, 2013, Argentina, personal communication).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…One of the most frequent reproductive organ disorders in female dogs is pyometra, which affects on average nearly 20% of all intact bitches before 10 years of age [1]. The disease is associated with inflammation and infection of the uterus leading to generalized illness.…”
Section: Introductionmentioning
confidence: 99%